2014
DOI: 10.4103/0019-557x.146278
|View full text |Cite
|
Sign up to set email alerts
|

Oral health promotion among rural school children through teachers: an interventional study

Abstract: The dramatic reductions in the OHI-S, PI, and GI scores in the group supplied with oral hygiene aids call for supplying low cost fluoridated toothpastes along with toothbrushes through the school systems in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 0 publications
2
69
0
Order By: Relevance
“…[91011121314] The results of the present study are comparable with studies that also showed that the dental health education programmes implemented through schoolteachers motivated and helped the children to adopt and maintain health practices and life styles.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…[91011121314] The results of the present study are comparable with studies that also showed that the dental health education programmes implemented through schoolteachers motivated and helped the children to adopt and maintain health practices and life styles.…”
Section: Discussionsupporting
confidence: 84%
“…The evidence from the studies suggested that simple instruction in oral hygiene could alter peoples’ behaviour in the short term. [101112131422]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, studies with groups that got any sort of OHE intervention vs controls concerning the Loe and Silness and O'Leary's plaque indices outcomes were analysed. In the cumulative analysis of five studies with both indices, there was a significant difference in the change of the Plaque Index favouring intervention groups, which showed a reduction in mean plaque levels (MD −0.36, IC 95%: −0.59 a −0.13) (Figure , Comparison 1).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies can be found in Table , which depicts the included studies’ the general characteristics. Among the 12 included studies, six were randomized by school, two by classroom and four by individuals …”
Section: Resultsmentioning
confidence: 99%